Penerapan Model Pembelajaran Project Based Learning Terhadap Kemampuan Berpikir Kreatif Siswa Pada Mata Pelajaran Pembuatan Busana Kerja Kelas XII Busana Di SMK NU Blawirejo Kedungpring - Syifana Isy Sabila; Peppy Mayasari; Imami Arum Tri Rahayu; Ma’rifatun Nashikhah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Project Based Learning is a learning model which provides opportunity for teachers to manage learning by involving project work. The aims of this research are 1) to determine the implementation of Project Based Learning model in subject making work clothes, 2) to determine the level of students creative thinking abilities in subject making work clothes, and 3) to find out students responses to the application of Project Based Learning in subject making work clothes. This research use quantitative descriptive with experimental methods. The research procedure consists the planning phase, implementation phase, and final research phase. The research instruments used were: 1) observation sheet, 2) test sheet, and 3) student responses questionnaire sheet. The results shown that 1) Project Based Learning model gets an average result of 84.3%, which is in the good category, 2) the results of the affective test got an average score of 72.51% in the creative category, and 3) students responses to application of the Project Based Learning model in subject of making work clothes got an average of 82.94% which was in the Very High category.